A new Afrotropical Ogovea (Opiliones, Cyphophthalmi) from Cameroon, with a discussion on the taxonomic characters in the family Ogoveidae - Giribet, Gonzalo; Prieto, Carlos E. (Zootaxa, 2003)
A new species of the genus Ogovea is described and illustrated, Ogovea cameroonensis n. sp. from Yaoundé. This species considerably enlarges the distribution range of the family Ogoveidae towards the Northeast. The new species, only known from its type locality in Cameroon, is the first described cyphophthalmid for that country. A new diagnosis for the family Ogoveidae is provided and a putative relationship of Ogovea with the South American genus Huitaca is rejected.